Hydrogen-rich syngas production and carbon dioxide formation using aqueous urea solution in biogas steam reforming by thermodynamic analysis. (14th April 2020) - Lin, Ke-Wei; Wu, Horng-Wen
Abstract: Biogas is a renewable biofuel that contains a lot of CH4 and CO2 . Biogas can be used to produce heat and electric power while reducing CH4, one of greenhouse gas emissions. As a result, it has been getting increasing academic attention. There are some application ways of biogas; biogas can produce hydrogen to feed a fuel cell by reforming process. Urea is also a hydrogen carrier and could produce hydrogen by steam reforming. This study then employes steam reforming of biogas and compares hydrogen-rich syngas production and carbon dioxide with various methane concentrations using steam and aqueous urea solution (AUS) by Thermodynamic analysis. The results show that the utilization of AUS as a replacement for steam enriches the production of H2 and CO and has a slight CO2 rise compared with pure biogas steam reforming at a temperature higher than 800 °C. However, CO2 formation is less than the initial CO2 in biogas. At the reaction temperature of 700 °C, carbon formation does not occur in the reforming process for steam/biogas ratios higher than 2. These conditions led to the highest H2, CO production, and reforming efficiency (about 125%). The results can be used as operation data for systems that combine biogas reforming and applied to solid oxide fuel cell (SOFC), which usually operates between 700 °C to 900 °C to generate electric power in the future. Highlights: Use of aqueous urea as replacement for steam enriches hydrogen production. To avoid carbon formation, the steam to biogas ratio should be greater than 2. At temperatures above 800 °C, CO2 formation is less than initial CO2 in biogas. We present trendlines of H2 and CO production with CH4 concentrations of biogas. Reforming efficiency of biogas blended with aqueous urea is higher than with steam.